Identification of the Main Intermediate Precursor of l-Ergothioneine Biosynthesis in Human Biological Specimens - Salvatore Sotgia; Arduino A. Mangoni; Mauro Forteschi; Rhys B. Murphy; David Elliot; Elisabetta Sotgiu; Gianfranco Pintus; Ciriaco Carru; Angelo Zinellu (Molecules, 2016)
A capillary electrophoresis coupled to tandem mass spectrometry (CE–MS/MS) has been used to make a qualitative determination of hercynine—the main precursor of l-ergothioneine biosynthesis—in some key human biological specimens, such as urine, whole blood, plasma, and saliva. From semiquantitative analysis results, the highest concentrations of hercynine were detected in saliva and whole blood, whereas much lower concentrations were measured in urine and plasma. Whole blood was the biological matrix with the highest concentration of l-ergothioneine followed by plasma, saliva, and urine. The antioxidant effects attributed to l-ergothioneine, along with its peculiar antioxidant mechanism, offer a possible explanation for the presence of the hercynine, as well as its concentration, in the considered biological matrices.